2013
DOI: 10.1007/s00431-013-2109-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between selected socioeconomic factors and basic anthropometric parameters of school-aged children and adolescents in Poland

Abstract: The aim of the present paper was to examine the associations between anthropometric parameters, overweight, obesity, and socioeconomic status (SES) of children and adolescents in Poland. Data were collected in the “Elaboration of reference blood pressure ranges for children and adolescents in Poland” OLAF-PL0080 (OLAF) study, a nationally representative survey on growth and blood pressure references for children and adolescents aged 7–18 years. Body height, weight, and waist circumference (WC) were measured, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
(25 reference statements)
5
21
0
1
Order By: Relevance
“…These clear gender differences in Korea are interesting because, in recent years, positive relationships between adiposity measures and SEP have become uncommon, particularly in developed countries [ 18 ]. A recent study conducted in Poland showed similar gender differences with respect to SEP in relation with WC and BMI [ 19 ]. Two explanations are possible.…”
Section: Discussionmentioning
confidence: 81%
“…These clear gender differences in Korea are interesting because, in recent years, positive relationships between adiposity measures and SEP have become uncommon, particularly in developed countries [ 18 ]. A recent study conducted in Poland showed similar gender differences with respect to SEP in relation with WC and BMI [ 19 ]. Two explanations are possible.…”
Section: Discussionmentioning
confidence: 81%
“…Considering three periods of development: childhood, early and late adolescence in boys the prevalence of overweight (from 19.19% to 19.64%) and obesity (from 5.56% to 4.87%) was similar, but in corresponding girls' groups prevalence of overweight (from 17.53% to 9.88%) and obesity (from 6.30% to 1.91%) has decreased in older age groups (Gomuła et al2015). A few studies have observed the following trend: families with higher socio-economic statuses had the most obese boys and the fewest obese girls (Jopkiewicz et al 2011, Gurzkowska et al 2014, Mladenova and Andreenko 2015. Brisbois et al (2011) 15 of the reviewed studies have found an association between fathers with low levels of education or employment status and adulthood obesity in their sons or daughters.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Specifically, maternal education could be more closely related to child health than paternal education. Some studies have shown a relatively greater contribution of maternal education to child health behaviour, 11 physical growth 12 and health care access. 13 To date, maternal education has been found inversely associated with blood pressure in children in three prospective Western cohort studies.…”
Section: Introductionmentioning
confidence: 99%